Determination of soil properties using thermogravimetry under laboratory conditions - Kučerík, Jiří; Svatoň, Karel; Malý, Stanislav; Brtnický, Martin; Doležalová‐Weismannová, Helena; Demyan, Michael S.; Siewert, Christian; Tokarski, David (European journal of soil science, 2020)
Analysis of soil properties and soil organic matter dynamics requires the use of reliable and rapid analytical techniques. Included in such applicable techniques is thermogravimetry (TG) which, typically, measures mass losses of soil heated during a temperature ramping. Previous work revealed relationships between mass losses of 10°C intervals (TG indicators) and total organic carbon (SOC), total nitrogen (TN) and clay content, and relationships between mass losses of larger temperature intervals (TG fractions) and interactions between SOC, TN and clay. However, widespread application of these relationships is hampered by the requirement to equilibrate soils at 76% relative humidity (RH) prior to and during TG measurements. In this study we tested whether the relationships between mass losses and soil properties can be observed at 43% RH by analyzing 37 mostly arable and grassland soils. It was found that at 43% RH the same TG indicators correlated significantly with soil properties as at 76% RH, but the correlations with TN and clay contents were observed at lower temperatures. New equations were developed for rapid analysis of soil properties using TG indicators and for determination of TG fractions at 43% RH. The results indicated that for routine application of these TG approaches in soil science, it is necessary to include an RH parameter that accounts for potential shifts in diagnostic temperatures when modelling the relationships between TG data and soil properties. Highlights Thermogravimetry data correlate with soil organic carbon, nitrogen and clay at 43% RH. Clay and nitrogen correlated at lower temperature compared to 76% RH. New equations applicable at laboratory conditions were developed. Wider use of TG requires including information on ambient moisture.